2016
DOI: 10.1111/ajt.13539
|View full text |Cite
|
Sign up to set email alerts
|

Successful Application of Closed-Loop Artificial Pancreas Therapy After Islet Autotransplantation

Abstract: Total pancreatectomy with islet auto-transplantation (TPIAT) may relieve the pain of chronic pancreatitis while avoiding post-surgical diabetes. Minimizing hyperglycemia after TPIAT limits beta cell apoptosis during islet engraftment. Closed loop (CL) therapy combining an insulin pump with a continuous glucose monitor (CGM) has never previously been investigated in islet transplant recipients. Our objective was to determine the feasibility and efficacy of CL therapy to maintain glucose profiles close to normog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Within transplantation, pancreas and islet recipients are likely to benefit from better training in relation to optimal insulin therapy and from greater understanding of the benefits of good glycaemic control. These patients also have an unprecedented opportunity to benefit from technological advances such as continuous glucose monitoring and closed‐loop insulin delivery introduced within closely monitored and heavily supervised hospital settings. Flash glucose monitoring boasts high accuracy, user‐friendliness and patient engagement, but is not currently licensed for use with insulin sliding scales in hospital settings.…”
Section: Future Trials and Technologies In Organ Donation And Transplmentioning
confidence: 99%
“…Within transplantation, pancreas and islet recipients are likely to benefit from better training in relation to optimal insulin therapy and from greater understanding of the benefits of good glycaemic control. These patients also have an unprecedented opportunity to benefit from technological advances such as continuous glucose monitoring and closed‐loop insulin delivery introduced within closely monitored and heavily supervised hospital settings. Flash glucose monitoring boasts high accuracy, user‐friendliness and patient engagement, but is not currently licensed for use with insulin sliding scales in hospital settings.…”
Section: Future Trials and Technologies In Organ Donation And Transplmentioning
confidence: 99%
“…This pilot study showed significant promise for safely maintaining euglycemic targets during the period of islet engraftment following islet transplantation with closed-loop insulin delivery. Moreover, the results of this study suggest that islet transplantation and closed-loop insulin delivery can be mutually complementary approaches, rather than competitive therapies [17]. …”
Section: Lessons From Clinical Islet Autotransplantationmentioning
confidence: 99%
“…26 This study marked the first clinical trial using the Medtronic Enlite 2 subcutaneous glucose sensors as part of a CL system. It was also one of the first studies to use CGM in a postsurgical patient population and in patients with some level of endogenous islet function.…”
Section: Introductionmentioning
confidence: 99%